2020
DOI: 10.3390/jmse8100751
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Chamber Configuration on the Hydrodynamic Efficiency of Oscillating Water Column Devices

Abstract: Based on the two-dimensional linear wave theory, the effects of the front wall thickness and the bottom profile of an Oscillating Water Column (OWC) device on its efficiency were analyzed. Using the potential flow approach, the solution of the associated boundary value problem was obtained via the boundary element method (BEM). Numerical results for several physical parameters and configurations were obtained. The effects of the front wall thickness on the efficiency are discussed in detail, then, various conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…By solving Equations ( 26), ( 28), ( 29), ( 33), (36), and (37), the unknown Fourier coefficients can be determined. Consequently, having evaluated the Fourier coefficients in each fluid domain for the diffraction, the motion-and pressure-dependent radiation problems, the corresponding velocity potentials can be determined (see Equations ( 15), (19), and ( 23)).…”
Section: Solution Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…By solving Equations ( 26), ( 28), ( 29), ( 33), (36), and (37), the unknown Fourier coefficients can be determined. Consequently, having evaluated the Fourier coefficients in each fluid domain for the diffraction, the motion-and pressure-dependent radiation problems, the corresponding velocity potentials can be determined (see Equations ( 15), (19), and ( 23)).…”
Section: Solution Proceduresmentioning
confidence: 99%
“…Theoretical and experimental studies of OWCs have been carried out in the literature, where most of the research concerns onshore and nearshore deployed devices installed on the seabed [10][11][12][13][14][15]. These devices are beneficial in terms of engineering deployment and maintenance costs compared to offshore OWCs [16][17][18][19][20]. However, wave energy operators worldwide are planning to move offshore due to a lack of available nearshore sites in heavily utilized zones where there are conflicts with other usages such as shipping, fishing, tourism, conservation, and recreation.…”
Section: Introductionmentioning
confidence: 99%
“…with i indicating the boundary node and j the boundary element. The boundary is then divided into curved quadratic elements, where φ and ∂φ/∂n are assumed to have three different values in each element, see [35]. The fluxes will then have a single nodal value for each element, as explained by [36].…”
Section: Boundary Integral Equationmentioning
confidence: 99%
“…A convergence study for both EEM and BEM was done prior to performing the computations of the results. For the calculations, the water depth is assumed to be 7.90 m, and a wave period T bounded by 2.50 ≤ T ≤ 30 s, as in [35]. In the case of the EEM, see Table 1, a convergence analysis for the maximum hydrodynamic efficiency η max is given for different values of the non-dimensional frequency Kh(= 0.5, 1.0, 1.5, 2.0, 2.5, 3.0 and 3.5).…”
Section: Convergence and Truncation Analysesmentioning
confidence: 99%
“…Results showed that air compressibility effects can diminish the predicted OWC efficiency up to about 20% in both Wells and impulse turbines. Rodríguez et al [17] proposed a numerical model to investigate the effects of the front wall thickness and the bottom profile of the OWC on the conversion efficiency performance. The numerical results revealed that a thinner front wall of the OWC can obtained wider efficiency band, but with less capacity to withstand the impact of storm waves.…”
Section: Introductionmentioning
confidence: 99%